2020
DOI: 10.1007/s00122-020-03571-7
|View full text |Cite
|
Sign up to set email alerts
|

A R2R3-MYB gene-based marker for the non-darkening seed coat trait in pinto and cranberry beans (Phaseolus vulgaris L.) derived from ‘Wit-rood boontje’

Abstract: Key message The gene Phvul.010G130600 which codes for a MYB was shown to be tightly associated with seed coat darkening in Phaseolus vulgaris and a single nucleotide deletion in the allele in Wit-rood disrupts a transcription activation region that likely prevents its functioning in this non-darkening genotype. Abstract The beige and white background colors of the seed coats of conventional pinto and cranberry beans turn brown through a process known as postharvest darkening (PHD). Seed coat PHD is attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 137 publications
(163 reference statements)
0
24
0
Order By: Relevance
“…This phenomenon has been most studied in pinto and cranberry beans but can be observed in other market classes. Lighter seed coats are perceived by consumers as indications of freshness or quality, so seeds exhibiting postharvest darkening have reduced market value ( Nasar-Abbas et al, 2009 ; Erfatpour and Pauls, 2020 ). The J locus was previously identified on Pv10, and genotypes that are homozygous recessive at J do not exhibit postharvest darkening ( Bassett, 2007 ; Elsadr et al, 2011 ; Erfatpour et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been most studied in pinto and cranberry beans but can be observed in other market classes. Lighter seed coats are perceived by consumers as indications of freshness or quality, so seeds exhibiting postharvest darkening have reduced market value ( Nasar-Abbas et al, 2009 ; Erfatpour and Pauls, 2020 ). The J locus was previously identified on Pv10, and genotypes that are homozygous recessive at J do not exhibit postharvest darkening ( Bassett, 2007 ; Elsadr et al, 2011 ; Erfatpour et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…MBW complex has been studied including R2R3-MYB, bHLH, and WD40 complex [ 59 ]. In Phaseolus vulgaris (Common bean), an R2R3 MYB was associated with seed coat darkening and involved in PAs oxidation and accumulation in the seed coat [ 79 ]. LACCASE family in Arabidopsis was involved in oxidative lignin polymerization and it was downstream of MYB46 and MYB58 [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bassett et al (2002) showed that the J gene was the genetic locus initiating the postharvest darkening in common beans while those with the recessive allele jj had no problems of postharvest darkening. On this note, Erfatpour and Pauls (2020) developed an R2R3-MYB gene-based marker obtained from "Wit-rood boontje" to aid bean breeders in the selection of non-darkening dry beans carrying the recessive jj genes in early generations as opposed to waiting to screen the phenotypic segregation. R2R3-MYB genes are known to regulate biosynthesis of proanthocyanidin (Erfatpour and Pauls, 2020).…”
Section: Genetic Breedingmentioning
confidence: 99%
“…On this note, Erfatpour and Pauls (2020) developed an R2R3-MYB gene-based marker obtained from "Wit-rood boontje" to aid bean breeders in the selection of non-darkening dry beans carrying the recessive jj genes in early generations as opposed to waiting to screen the phenotypic segregation. R2R3-MYB genes are known to regulate biosynthesis of proanthocyanidin (Erfatpour and Pauls, 2020).…”
Section: Genetic Breedingmentioning
confidence: 99%